KONSEP DASAR SISTEM DATA GOVERNANCE DALAM ERA DIGITALISASI - Isnaini Nur Harahap; Khoirunnisya Gita Segara; Syahnazwa Aiska Hidayat Hutasuhut; Nurbaiti Nurbaiti (JOURNAL SAINS STUDENT RESEARCH, 2025)
Currently the industrial world has entered into a digital era where companies must adapt all their activities to digital technology, one of which is to create a company data system with good governance and adhere to the principle of transparency in data as well as the value of accountability in the data owned. Information and Communication Technology is very important in reviewing data to ensure that the data owned by the company is well systematized and directed to achieve one company goal. This research uses a descriptive qualitative method where this method was chosen to explore in depth the basic concepts of data governance systems in the digitalization era through narrative and interpretative analysis of relevant literature and documents. In addition, the data obtained in this study were obtained from the results of data collection which included scientific journals, books, and policy reports that discussed topics related to data governance and digital transformation. So that the data to be analyzed can provide an overview of the main principles, challenges, and opportunities related to the implementation of digital governance in an organizational or corporate environment. The implementation of a data governance system in the digitalization era is a strategic step that must be taken by every organization or company to ensure the accuracy, security, and consistency of its data. Therefore, the application of technologies such as Artificial Intelligence (AI) and Machine Learning (ML) is very important in supporting the process of automatic data classification, detecting anomalies, and providing insight for strategic decision making. The digital era poses great challenges regarding the protection of personal data, especially with increasing regulations such as the Personal Data Protection Act (PDP) and the General Data Protection Regulation (GDPR) that require organizations to take responsibility for the data they manage. Therefore, the growing digitalization must be balanced with the implementation of strong data governance principles so that every data-based managerial process can run in an accountable and standardized manner